Risk Factors for Stress Fractures in Athletes - Aleksandra Minda; Barbara Anna Zapalska; Antonina Teresa Witkowska; Julia Piotrowska; Aleksandra Łubińska-Kowalska; Adrianna Domańska; Adrianna Witkowska; Monika Wendland; Krzysztof Julian Długosz; Justyna Janikowska (Quality in Sport)
Introduction